Social innovation matters: The adoption of participatory guarantee systems within Italian alternative agri‐food networks2. (2nd July 2019) - Sacchi, Giovanna
Abstract: Participatory guarantee systems are locally based practices for assuring organic product authenticity that are proving to be a valuable tool for farmers' empowerment and social innovation. Recent years have witnessed a growing interest in locally based certification and distribution strategies of organic products. Participatory guarantee systems (PGS) simplify bureaucratic procedures for small organic producers, who are often overwhelmed by the extensive documentation required by third‐party certification. PGS development has facilitated several social processes, thus enabling social inclusion, farmers' empowerment, and mutual support.